Bio-based composites fabricated from wood fibers through self-bonding technology. (January 2022) - Ye, Haoran; Wang, Yang; Yu, Qinghan; Ge, Shengbo; Fan, Wei; Zhang, Minglong; Huang, Zhenhua; Manzo, Maurizio; Cai, Liping; Wang, Lishu; Xia, Changlei
Abstract: Green composite processing technology of wood fibers is an inevitable choice for global sustainable development. In this research, waste poplar powder with different particle sizes was used to prepare glue-free biocomposites with good mechanical and waterproof properties by hot-molding. The biocomposites made of larger size wood powder had better tensile strength (40.3 MPa) and the biocomposites made of smaller size wood powder had the greater bending strength (50.5 MPa). The thickness swelling rate of the biocomposites was only 4.26% after soaking in water for 24 h. The cross-section morphology of the biocomposites showed that the cell wall collapses enhanced the interfacial bonding. Chemical analysis showed that lignin repolymerized with cellulose and hemicellulose for the vitrification transition. In addition, the biocomposites with excellent mechanical properties had no formaldehyde release, which can replace the traditional density boards made of adhesives and applied as furniture materials and in line with the concept of cleaner production. Graphical abstract: Image 1 Highlights: Glue-free biocomposite were prepared from poplar powder with different particle sizes by hot molding. Prepared biocomposites have better physical/mechanical properties compared to medium- or high-density fiberboards. Cell wall collapses enhanced mechanical bonding of fibrous components. The 24-h water absorption of prepared biocomposites was 4.26% much lower than other wood-based materials. Depolymerization and repolymerization of lignin enhanced hydrogen bonding components